2010
DOI: 10.1007/s00167-010-1219-9
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis following TKA: comparison of conventional technique, computer-assisted navigation and minimally invasive technique combined with computer-assisted navigation

Abstract: the results of the study confirm that navigation does not influence the length of rehabilitation. However, in case of minimal invasive surgery, rehabilitation is faster than in Groups I and II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 20 publications
7
22
1
2
Order By: Relevance
“…Patients in groups I and II can be assumed to reproduce comparable lower limb coordinated movement despite decreased flexibility of joints on the affected side due to the increased flexibility of other joints in the kinetic chain, which represent an important role in compensation. This result is similar to the results of earlier studies [3]. The reduced variability of hip and knee motion on the affected side and the increased variability of knee and hip motion on the unaffected side and pelvis predict gait instability [2,11] and an increased risk of falling [4,10,17,30].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients in groups I and II can be assumed to reproduce comparable lower limb coordinated movement despite decreased flexibility of joints on the affected side due to the increased flexibility of other joints in the kinetic chain, which represent an important role in compensation. This result is similar to the results of earlier studies [3]. The reduced variability of hip and knee motion on the affected side and the increased variability of knee and hip motion on the unaffected side and pelvis predict gait instability [2,11] and an increased risk of falling [4,10,17,30].…”
Section: Discussionsupporting
confidence: 92%
“…The increased variability of knee and hip joints on the unaffected side and increased variability of pelvis tilting and rotation represent increased articular flexibility and greater roles in ensuring stability [2,34] (Table 4). The results confirmed that these joints played an important role in compensation [3]. Pelvis flexion-extension did not play a role in compensation because the mean CV for pelvis flexion-extension was similar to that of the control group ( Table 4).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ennek egyik fontos eszköze lehet a mozgáselemzéssel mért járásparaméterek értékelése. A térdízületi kopás és a teljes térdízületi protézis lényegesen megváltoztatja a járás paramétereit 1,2,3,4 , a járás változékonyságát és stabilitását 5,6,7,8,9 . A járásvizsgálatok térdízületi protézis beülte-tése el tt vagy utána 6, 12 hónappal végezhe-t k, mivel a járásváltozékonyság vizsgálatához szükséges hosszú idej (minimum 10 perc id tartamú) futószalagon végzett járásvizsgá-lat csak a poszt operatív 6. hónaptól végezhet .…”
Section: Bevezetésunclassified
“…Jelen kutatásban ez azt jelenti, hogy a nem érintett oldali térdízület, medenceöv, valamint a vállöv is a kompenzációs mechanizmus része, segít a járás stabilitásának biztosításában. Ez a korábbi megállapításokat is alátámasztja, azaz a nem érintett térdízület és a medenceöv fontos szerepet játszik a kompenzációban mind a m tét el tt, mind a m tét után 1,6,7 . Az eredményeink arra is felhívják a fi gyelmet, hogy a korai posztoperatív id szakban ezeken az ízületeken kívül a vállövnek is fontos szerepe van a kompenzációban, a biztonságos járás létrehozásában.…”
Section: Mozgásvizsgálat éS -Terápiaunclassified